Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep39048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism: the human dopamine transporter histidine 547 regulates basal and HIV-1 Tat protein-inhibited dopamine transport

Abstract: Abnormal dopaminergic transmission has been implicated as a risk determinant of HIV-1-associated neurocognitive disorders. HIV-1 Tat protein increases synaptic dopamine (DA) levels by directly inhibiting DA transporter (DAT) activity, ultimately leading to dopaminergic neuron damage. Through integrated computational modeling prediction and experimental validation, we identified that histidine547 on human DAT (hDAT) is critical for regulation of basal DA uptake and Tat-induced inhibition of DA transport. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(67 citation statements)
references
References 72 publications
(113 reference statements)
8
55
4
Order By: Relevance
“…Based on the constructed hDAT-Tat binding model in our previous work 20 , hDAT residues Y88, K92, and H547 could form hydrogen bonds with residues K19, P18, and R49 of HIV-1 Tat, respectively. According to our previous computational and experimental results, single mutation of either hDAT Y88 (Y88F), K92 (K92M) or H547 (H547A) could significantly attenuate the binding between DAT and Tat 17,18 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Based on the constructed hDAT-Tat binding model in our previous work 20 , hDAT residues Y88, K92, and H547 could form hydrogen bonds with residues K19, P18, and R49 of HIV-1 Tat, respectively. According to our previous computational and experimental results, single mutation of either hDAT Y88 (Y88F), K92 (K92M) or H547 (H547A) could significantly attenuate the binding between DAT and Tat 17,18 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Using computational modeling and experimental approach, we have identified several key residues on human DAT (hDAT), which are crucial for Tat-hDAT interaction and dynamic transport process 9 . Furthermore, we have demonstrated that in vitro exposure to Tat reduced reuptake of DA via hDAT in cells 1618 and rat striatal synaptosomes 19 . The inhibitory effect of Tat on DAT function results from Tat directly interacting with DAT 16,20,21 .…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…When examining the neurotoxic effects of Tat it is also important to consider the role of disruptions in healthy dopamine signaling. A potential alternative/complementary explanation for the effects that we have observed stems from Tat’s ability to bind and inhibit dopamine transporter activity (DAT) (Quizon et al, 2016) leading to increased dopamine levels which could contribute to neurotoxic conditions. Interestingly, human DAT activity in HIV-1 patients negatively correlates with HAND symptom severity (Wang et al, 2004; Chang et al, 2008) suggesting it plays an important role in the development of HAND pathology.…”
Section: Resultsmentioning
confidence: 99%